This way to books - Bauer, Caroline Feller (Bronx, N.Y. : Wilson, 1983)
Presents a collection of ideas, programs, techniques, and activities designed to involve children in books and to extend their reading experience by making reading irresistible and fun.
Includes bibliographies and index.
Booklist.
Elem. School Library Collection.
Wilson's Children.
Professional
Keywords: Children -- Books and reading -- Handbooks, manuals, etc; Children -- Books and reading